Pengaruh likuiditas, ukuran perusahaan, profitabilitas, dan struktur modal terhadap nilai perusahaan - Wijaya, Nawang Sari; Fitriati, Ika Rosyada (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The principal objective of the company is to build the worth of the company. The importance of company value because high company value will bring high investor growth. The worth of the company is also known as market capitalization, because if the company’s stock price increases, the value of company can bring the best developments for investors. The study is expected to analyze and test the effect of liquidity, firm size, profitability, and capital structure on firm value. The populace utilized in this study are Property and Real Estate companies recorded on the Indonesia Stock Exchange (IDX) in 2016-2020 with a final sample of 197. The sample method used in this research is multiple linear regression analysis use the IBM SPSS 26 program. The conclusion this is research simultaneously the variables of liquidity, firm size, profitability, and capital structure have an effect on firm value. While partially for liquidity variable has a negative effect in firm value, firm size and profitability have a positive effect on firm value, while capital structure has no effect on firm value.